2022
DOI: 10.1038/s41598-022-09822-5
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of thyroid imaging reporting and data system combined with BRAFV600E mutation analysis in Bethesda categories III–V thyroid nodules

Abstract: Fine needle aspiration biopsy is a crucial method for preoperative diagnosis of thyroid nodules. However, thyroid nodules classified as Bethesda categories III–V cannot obtain definite cytological results. Our aim was to study the diagnostic value of thyroid imaging reporting and data system combined with BRAFV600E mutation analysis in Bethesda categories III–V thyroid nodules, so as to provide more precise direction for the follow-up treatments. A total of 174 Bethesda categories III–V thyroid nodules perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
2
1
0
Order By: Relevance
“…Our data indicated that, compared to a single US-FNAB, its combination with BRAF V600E mutation performed a significantly higher accuracy and sensitivity, whereas a comparable specificity in predicting PTC among macro-calcified thyroid nodules. Similar results have also been reported previously in some researches involving thyroid nodules (not limited to macro-calcified nodules) [ 8 , 21 , 23 ]. However, one of the disadvantages of our study was that we did not compare the diagnostic value of US-FNAB combined BRAF V600E to CNB, which was another screening test with both high sensitivity and specificity, because some of the recent reports indicated that CNB showed greater diagnostic performance and ought to be considered first to improve diagnostic efficiency when evaluating entirely calcified types of macro-calcified nodules [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our data indicated that, compared to a single US-FNAB, its combination with BRAF V600E mutation performed a significantly higher accuracy and sensitivity, whereas a comparable specificity in predicting PTC among macro-calcified thyroid nodules. Similar results have also been reported previously in some researches involving thyroid nodules (not limited to macro-calcified nodules) [ 8 , 21 , 23 ]. However, one of the disadvantages of our study was that we did not compare the diagnostic value of US-FNAB combined BRAF V600E to CNB, which was another screening test with both high sensitivity and specificity, because some of the recent reports indicated that CNB showed greater diagnostic performance and ought to be considered first to improve diagnostic efficiency when evaluating entirely calcified types of macro-calcified nodules [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 91%
“…Fnais et al [46], in their meta-analysis, did not find any substantial evidence to support the implementation of BRAF mutation analysis as a single screening test for patients with indeterminate thyroid nodules (categories III-V together or separately in category III nodules). However, several authors agree that the combined assessment of the BRAF mutation and ultrasound risk can be effectively used in the diagnosis of BSRTC category III nodules [47,48]. Our analyses confirmed this opinion, but only with respect to AUS-nuclear nodules.…”
Section: Discussionsupporting
confidence: 73%
“…It is a challenge facing clinicians to distinguish thyroid cancers from benign nodules to ensure that each patient receives timely and appropriate treatment [11]. The ne needle aspiration cytology (FNAC) has proven useful in assessing the likelihood of malignant tumors [12,13]. However, the sample collection and interpretation of thyroid smears can be intractable and require experience.…”
Section: Introductionmentioning
confidence: 99%